Analisis Penerapan Kesantunan Berbahasa Dalam Podcast Deddy Corbuzzier “GUS MIFTAH MARAH !INI JELAS HINA NABI MUHAMMAD !ANW ROHINGNYA BAGAIMANA GUS!?” - Shifa Aulia Putri (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Talking or chatting is an activity that humans do in their daily lives. In a conversation or discussion, everyone should apply polite language. Language politeness also has different applications, such as for interlocutors who are younger than us, older and on the same level as us. Apart from looking at age, language politeness is also usually related to a person's rank so that its application varies. So the aim is to analyze the politeness of language contained in Deddy Corbuzzier's podcast entitled